Economic evaluation of mass screening as a strategy for hepatitis C virus elimination in South Korea - Hwa Young Choi; Kyung-Ah Kim; Bo Young Park; Bo Youl Choi; Moran Ki (Journal of Infection and Public Health)
Background: This study examines Hepatitis C virus (HCV) screening scenarios to meet World Health Organization (WHO) elimination targets (incidence ≤5 per 100,000, mortality ≤2 per 100,000) and assesses their timeframes and cost-effectiveness. Methods: A closed cohort model of Koreans aged 30–79 in 2020 projected HCV incidence and mortality over 20 years. Economic evaluations used a dynamic transmission model, considering prevalent and annual incident cases. This approach addresses the limitations of previous models that neglected annual new HCV infections. Nine scenarios with varying screening intervals were created considering health checkup uptake, treatment rates, and HCV incidence reduction. Economic evaluations from the healthcare system's perspective employed cost-utility and cost-benefit analyses. Results: Without national HCV screening, incidence slightly decreases, whereas mortality triples over 20 years. Introducing HCV screening offers five scenarios to meet WHO targets in 20 years. The quickest, involving biennial screening, high uptake, and a 30% incidence reduction, meets the incidence target at 6 years and mortality target at 14 years. For the most cost-efficient scenario, screening every 4 years with moderate uptake and a 20% incidence reduction meets the incidence target at 17 years and mortality target at 18 years. The Incremental Cost-Effectiveness Ratio (ICER) is $8,867 per quality-adjusted life-year (QALY), with a Benefit-Cost Ratio (BCR) of 1.60. Conclusion: The absence of HCV screening impedes elimination goals and increases mortality. Biennial screening, with high participation and treatment rates, rapidly achieves targets but is less economically efficient. Screening every 4 years with moderate uptake and treatment rates is economically feasible and meets elimination goals within 20 years. Rapid screening implementation is crucial for effective HCV elimination.